Effects of textual glosses on text comprehension, vocabulary gain and vocabulary retention among tertiary level Persian-speaking ESL learners - Azari, Foroogh (2013)
The present study investigated the effects of textual glosses on reading comprehension and vocabulary learning among tertiary level Persian-speaking ESL learners. In the present quasi-experimental research, 76 postgraduate ESL students at UPM who had attained similar scores in a standardized reading test were divided into four groups randomly before they attempted a pre-test and read six authentic texts under one of for conditions: L1 gloss, L2 gloss, L1 and L2 gloss, and no gloss. After reading each text, the students were asked to write recall protocols based on what they remembered about the text. After a period of five weeks, an immediate post-test as well as a (subsequent) delayed post-test were administered to assess students‟ vocabulary gain and vocabulary retention in terms of the 30 target words. The results revealed that participants in the experimental (L1 gloss, L2 gloss, and L1 and L2 gloss) groups outperformed those in the control (no gloss) group in text comprehension, but the recall protocol scores obtained by the gloss groups were not significantly different statistically. Furthermore, the results revealed that the combination of L1 and L2 gloss was the most effective gloss condition in enhancing vocabulary gain and vocabulary retention, followed by L1 gloss, and L2 gloss. However, exploratory attempts to correlate reading motivation type with text comprehension, vocabulary gain, and vocabulary retention produced a mixed bag of positive and negative relationships between these variables of interest under certain gloss conditions, thereby indicating a need for further study. In the qualitative phase of the study, the analysis of online interviews revealed that the majority of the participants in experimental and control groups preferred to read glossed texts to non-glossed texts. Most of the participants declared that they preferred not to refer to a dictionary since it was time-consuming, difficult, and boring and they could not enjoy reading when they had to regularly look up words in this way. The participants who read the glossed texts had a positive attitude toward the reading activity. The participants in the experimental groups also reported that they preferred to read L1 and L2 glossed texts, L1 glossed texts, and L2 glossed texts, in that order of preference. Furthermore, the majority of participants in the experimental groups indicated that they tended to continue reading outside the English class while the subjects in control group were not motivated to do so. Overall, the results of the present study were deemed to provide further support to the findings of previous studies in the area of incidental vocabulary acquisition through reading in addition to providing some validation to Schmidt‟s (1990) noticing hypothesis, Anderson‟s (1984) schema theory, and Paivio‟s (1991) dual coding hypothesis. The study therefore concluded that the provision of textual glosses does indeed enhance reading comprehension and acquisition of vocabulary knowledge of second language learners. Furthermore, the results of this study revealed that even relatively complex reading passages enhanced by the provision of L1 gloss, L2 gloss, or L1 and L2 gloss can be assigned to tertiary level ESL/EFL learners to help them become efficient readers and motivate them to continue reading independently outside their English class.